Tactical hedging as coalition-building signal: the evolution of Quad and AUKUS in the Indo-Pacific - Koga, Kei (2024)
How are the rise, fall, and evolution of minilateralism in the Indo-Pacific region explained? To address this question, I examine the cases of the Quad and AUKUS, and argue that they were caused by the success and failure of coalition-building efforts made through ‘tactical hedging’. As the world transitions from a unipolar to a non-unipolar world, states attempt to formulate coalitions to safeguard their national interests. However, the challenge is to figure out which states are truly ‘like-minded’ and can strategically coordinate their policies for mutual interests. Under this circumstance, states send signals through ‘tactical hedging’ – ‘an ambiguous, temporal declaratory policy doctrine’ – that assists the hedger in assessing whether its allies and partners are willing to cooperate; in this case, building a coalition towards the same or similar strategic objectives. The key is the initial ambiguity in signalling, which becomes critical to the future success of building a coalition among parties whose interests are not always congruent.